Neuromuscular fatigue development and biomechanical changes during constant-load, high-intensity cycling exercise - Overton, A. J.; Abbiss, C.; Blazevich, A. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Neuromuscular function during fatiguing exercise has primarily been examined at the onset and termination of an exercise bout. However this does not capture the time course, or relative contribution, of central and peripheral fatigue mechanisms and assumes a linear progression to exhaustion. Importantly, associated biomechanical (muscle activity and kinematic) changes have not been simultaneously investigated. Methods Nine well trained male cyclists performed seven testing sessions; session 1: incremental cycling test to exhaustion; session 2: constant-load cycling time to exhaustion (TTE) test; sessions 3-6: constant-load cycling tests to 20, 40, 60 and 80% (T20-T80) of the time taken to complete the TTE test (T100) in random order; session 7: a TTE test. Cycling tests were performed at a constant cadence (89 ± 10 rpm) at 90% Pmax (PO that elicits a VO2 reading < 2.1 ml/kg/min of the subsequent reading despite increasing workload; 337 ± 38 W). EMG activity of seven lower limb muscles and 3D joint kinematics were recorded at the beginning (T0) and termination (T100) of the first TTE test, and in the final 20 s of the remaining constant-load cycling tests (T20-T80). Neuromuscular assessments (mechanical and EMG responses of the quadriceps to voluntary and electrically stimulated (femoral nerve) contractions) were made before and after exercise. Results The participants cycled for 5:49 ± 0:51. Twitch contraction time increased to T20, and peak twitch torque and the average rate of torque development and relaxation increased to T40 then declined to T100. Neither M-wave amplitude (Mmax) and duration nor twitch one-half relaxation time changed. No changes were observed in peak torque and the rate of torque development measured during voluntary knee extension. Increases in vastus lateralis EMG amplitude and EMG:Mmax from T80-T100 were not significant. No significant changes were observed in %VA, peak EMG amplitudes, rate of EMG rise or EMG mean frequency (MeanF). During cycling, EMG onset and offset times and duration did not change, although peak vastus medialis and gluteus maximus (GMax) EMG amplitude, GMax mean EMG amplitude and GMax EMG impulse significantly increased. No significant changes were observed for EMG MeanF. Increases in trunk flexion from T60, trunk lateral flexion and hip abduction/adduction from T80 and trunk lateral flexion and knee valgus/varus at T100 were observed. Discussion Peripheral neuromuscular fatigue mechanisms developed early in the exercise bout and were significant by T60, but were temporarily dissociated from significant kinematic changes. As the exercise bout progressed, efferent drive to the muscle increased from T80-T100 and was associated with a significant change in kinematics at the trunk, hip and knee joints.